PENYULUHAN DAN SIMULASI BANTUAN HIDUP DASAR (BHD) PADA REMAJA DI SMAN 1 WATANSOPPENG - Andi Yulia Kasma; Rahma Yulis; Andi Ayumar; Ahmad Surya Pratama (LPPM STIK Makassar, 2021)
ABSTRACT Emergency events usually take place quickly and suddenly so that it is difficult to predict when they will occur. Emergency is a life-threatening condition that requires quick help, precisely and accurately and accurately. Victims of cardiac arrest can be up to when doing worship activities, such as recitation, listening to lectures, or even in other places of worship. Help must be done immediately to prevent more severe brain damage. The design of this community service activity is the socialization and simulation of BHD actions for unconscious victims due to cardiac arrest. The participants were new students at Senior High School 1 Watansoppeng , amounting to 300 people. The participants were very enthusiastic and took turns trying to simulate each other. Not only enthusiastic in the simulation, participants also continued to actively ask. Some testimonies from participants that this simulation is very useful, because not only general science they always learn, but also world knowledge about health which will be useful for others Keywords : BHD, henti jantung, penyuluhan, simulasi